2013
DOI: 10.1111/aje.12063
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Broussonetia papyrifera (L.) vent. on community characteristics in the forest and forest–savannah transition ecosystems of Ghana

Abstract: Following its introduction in the late 1960s, Broussonetia papyrifera L. Vent. Moraceae (paper mulberry) has emerged as a major exotic invasive species in Ghana's forest ecosystems. This study was carried out to assess the effects of B. papyrifera invasion on community composition in forest and forest–savannah transition ecosystems. Comparative and removal experiments were conducted in paired B. papyrifera invaded versus uninvaded plots. In the comparative assessment, species composition was found to be simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Furthermore, Bahati et al (2008) also reported a 30% cover abundance MFR by this tree species. Broussonetia papyrifera tree species has a tendency towards hampering the abundance of other indigenous broadleaf species growing in association with it (Bosu et al, 2013),hence can be considered as an invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bahati et al (2008) also reported a 30% cover abundance MFR by this tree species. Broussonetia papyrifera tree species has a tendency towards hampering the abundance of other indigenous broadleaf species growing in association with it (Bosu et al, 2013),hence can be considered as an invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…B. papyrifera is a shade‐intolerant species, and thus competes with native pioneers for similar resources and space; its superior reproduction, survival and growth traits increase its competitiveness and dominance over native pioneer species (Bosu et al. ). For instance, B. papyrifera grows rapidly, and at maturity, its canopy can create deep shade, which may suppress establishment and growth of native pioneers (Apetorgbor & Bosu ; Bosu et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, B. papyrifera grows rapidly, and at maturity, its canopy can create deep shade, which may suppress establishment and growth of native pioneers (Apetorgbor & Bosu ; Bosu et al. ). Moreover, B. papyrifera regenerates from seed, suckers and stumps (Sheil & Van Heist ; Kyereh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Broussonetia papyrifera is a light-demanding tree that colonizes forest gaps and is eliminated when gaps close up. In Africa, it is an invasive alien species that reduces cover of native species, but does not seem to reduce overall species richness of forests (Bosu et al 2013). Broussonetia papyrifera accounted for 56 percent of all seeds and was particularly abundant aboveground in the younger secondary stands (mean 4.6 individuals per plot, SD 4.7), but was even present at low density in the older growth (mean 1.0 individual per plot, SD 0.9) despite being relatively recently introduced (not mentioned in extensive surveys made in 1993-1994 by J. Lwanga and others; Davenport et al 1996).…”
Section: Discussionmentioning
confidence: 99%